A phospho-switch controls RNF43-mediated degradation of Wnt receptors to suppress tumorigenesis - Tadasuke Tsukiyama (Nature Portfolio, 2020)
RNF43 is frequently mutated in cancers and negatively regulates Wnt signalling. Here, the authors report that RNF43 phosphorylation at a serine triplet is required for the negative regulation of Wnt signalling and that the phosphorylation of RNF43 suppresses cancer-associated oncogenic RNF43 mutants.